2010
DOI: 10.1080/17470211003802434
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Saccades and Response Type on the Simon Effect: If you Look at the Stimulus, the Simon Effect May be Gone

Abstract: The Simon effect has most often been investigated with key-press responses and eye fixation. In the present study, we asked how the type of eye movement and the type of manual response affect response selection in a Simon task. We investigated three eye movement instructions (spontaneous, saccade, and fixation) while participants performed goal-directed (i.e., reaching) or symbolic (i.e., finger-lift) responses. Initially, no oculomotor constraints were imposed, and a Simon effect was present for both response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 40 publications
2
25
0
Order By: Relevance
“…These conclusions are supported by a recent study by Buetti and Kerzel (2010), in which the authors tested in a standard Simon task the influence of eye movements (or fixed gaze) as a function of two types of responses. Crucially, in the scenario comparable to the present study-the pointing response combined with a fixed gaze-a spatial compatibility effect was observed.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…These conclusions are supported by a recent study by Buetti and Kerzel (2010), in which the authors tested in a standard Simon task the influence of eye movements (or fixed gaze) as a function of two types of responses. Crucially, in the scenario comparable to the present study-the pointing response combined with a fixed gaze-a spatial compatibility effect was observed.…”
Section: Discussionsupporting
confidence: 63%
“…In a previous study, Buetti and Kerzel (2010) investigated the impacts of different response modes (a finger lift and a pointing gesture) and gaze conditions (fixed gaze, free eye movements, and a saccade toward the stimulus) on a standard Simon task. They observed that the pointing gesture systematically caused a spatial compatibility effect in the fixed-gaze and free-eye-movement conditions, but not in the saccade condition.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…His hands lay on the screen, just below the boxes where stimuli were displayed ( Figure 1B). This finger-lift action was shown to be comparable with more common button-press responses (Buetti & Kerzel, 2010; see also Buetti & Kerzel, 2009).…”
Section: Task and Stimulisupporting
confidence: 55%
“…For instance, in the Simon task literature, the reach-to-touch paradigm has already been used to investigate temporal properties of the effect (Porcu et al, 2016;Buetti & Kerzel, 2010;Finkbeiner & Heathcote, 2016). In a typical design, participants may be presented with a cognitive task that requires a speeded choice between two or more response alternatives.…”
Section: Reach-to-touch Paradigmmentioning
confidence: 99%